Mutation of the Na+/K+-ATPase Atp1a1a.1 causes QT interval prolongation and bradycardia in zebrafish - Pott, Alexander; Frese, Karen S. (Journal of molecular and cellular cardiology, 2018)
The genetic underpinnings that orchestrate the vertebrate heart rate are not fully understood yet, but of high clinical importance, since diseases of cardiac impulse formation and propagation are common and severe human arrhythmias. To identify novel regulators of the vertebrate heart rate, we deciphered the pathogenesis of the bradycardia in the homozygous zebrafish mutant hiphop (hip) and identified a missense-mutation (N851K) in Na+/K+-ATPase α1-subunit (atp1a1a.1). N851K affects zebrafish Na+/K+-ATPase ion transport capacity, as revealed by in vitro pump current measurements. Inhibition of the Na+/K+-ATPase in vivo indicates that hip rather acts as a hypomorph than being a null allele. Consequently, reduced Na+/K+-ATPase function leads to prolonged QT interval and refractoriness in the hip mutant heart, as shown by electrocardiogram and in vivo electrical stimulation experiments. We here demonstrate for the first time that Na+/K+-ATPase plays an essential role in heart rate regulation by prolonging myocardial repolarization.